Les halles à marée françaises au temps du confinement en 2020 - Frédérique Alban; Sophie Léonardi; Pascal le Floc’h (Développement Durable et Territoires)
The question raised concerns the capacity of the fish markets to adapt to the fluctuations in supply and fish prices caused by the first confinement and amplified by the second in 2020. The national turnover of the first markets declined by 18 % compared to the average of the previous three years. The method of breaking down turnover shows that the value of production reflects a strategy on quantity and more rarely a price policy. Surveys of fish market managers provide a complementary even different understanding to that of the sales statistics. The discussion of the results raises two major questions. The first deals with the informational bias when the analysis is limited to a quantitative approach to production statistics. The second is the question of the potential threat of direct sales to fish markets.